Analisis Kelayakan Finansial Usaha Roti Labu Kuning Di Kabupaten Ketapang Kalimantan Barat - Arianti, Ira; Dwi Hastuti, Ningrum; Cholid, Irfan; Mamel Lahagu, Jovan (Politeknik Negeri Ketapang, 2022)
The addition of yellow pumpkin to the bread making process is a form of product innovation aimed at reducing the use of flour and increasing the use of pumpkin and adding nutritional value to the product. Therefore the financial analysis of the yellow pumpkin bread business is of particular important. It was revealed that the Break Even Points was 4155 packs. the Net Present Value was positive of Rp 104.917.412, the Internal Rate of Return was 39% greater than the MARR, The B/C Ratio was 1.46 and the Payback Period of 2.2 years did not exceed the planned business period.. Therefore, based on the financial analysis, the yellow pumpkin bread business is feasible and worth to develop.